Local Ecology-Based Agroforestry Management: Building Effectiveness of Knowledge-Based Wetland Management - Dadi Dadi (Jurnal Mantik, 2019)
One of the advantages and knowledge possessed by local communities in various parts of Indonesia is the use of local ecology-based agroforestry systems. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the application of agroforestry systems developed by farmers in Indonesia has quite a lot of impact on various sectors of human life. life, in addition to bringing many benefits in the form of materials and crops. The use of agroforestry systems is also a local technology that has been passed down from generation to generation, and is very suitable for various plants and plants that live in various tropical forests in Indonesia, while several trials have been applied to agroforestry techniques that have been carried out. by the community includes land preparation, water management, soil fertility management and evaluation of crop yields, while local wisdom is the result of a learning process based on farmers' perceptions in managing the various advantages of available natural resources. in Indonesia country.